Effect of repeated freezing and thawing on the quality of beef liver - Salam, MA; Khatun, H; Akter, H; Ahmed, MT; Hashem, MA; Khan, M (Meat Research, 2025)
The present study investigated the effect of repeated freeze-thaw cycle on the quality of beef liver. For this purpose, raw fresh beef liver was collected and divided into four treatments groups- Day 1 (T1 - fresh group, which was immediately analyzed) and other packed portions were stored under refrigeration at 4℃ for the whole day (12 hours) and at evening, stored under freezing at -20℃. Analyses of other samples were performed next 2nd (T2, freeze-thaw), 3rd (T3, freeze-thaw) and 4th (T4, freeze-thaw) day with three replicates. Liver sample was packaged in polythene bags and frozen at -20℃ for overnight (12 hours) followed by thawing in refrigerator at 4℃ for whole day (12 hours). The freeze-thawed procedure was repeated for subsequent for four days. The sensory tests (color, odor, juiciness, and tenderness), the proximate components dry matter (DM), crude protein (CP), ether extract (EE) and ash, physicochemical properties (pH and cooking loss), biochemical properties free fatty acid (FFA%), Peroxide value (POV meq/kg) and Thiobarbituric acid (TBARS mg-MDA/kg), and the microbial assessments, total viable count (TVC log cfu/g) were carried out for each treatment. The result showed that color, odor, juiciness, and tenderness were significantly (p<0.05) decreased with the increase of freeze-thawed cycle. Dry matter and ash content were significantly (p<0.05) increased, whereas crude protein and ether extract were decreased with the increase of freeze-thaw cycle. pH and water holding capacity were decreased and cooking loss was increased with the increase of freeze-thaw cycle (p<0.05). Thiobarbituric acid values were increased (p<0.05) with the increase of freeze-thaw cycle. Microbial assessments like TVC values were increased (p<0.05) with the increase of freeze-thawed cycle. With the increased freeze-thaw cycle decreasing the quality in all parameters studied were found. Thereby, avoiding of repeated freeze-thaw cycle is more acceptable. In conclusion, these findings have been suggested that shelf life of raw beef liver freeze at -20℃ and thaw at 4℃ for whole day up to maximum three days could be acceptable.